Model Evangelisasi Paulus di Efesus (Kisah Para Rasul 19:1-12) dan Kontribusinya bagi Evangelisasi Modern - Kristiyanto, Nikolas; Suharyono, Henrikus (Sekolah Tinggi Teologi Berita Hidup, 2023)
In the history of Christianity, evangelization is a very important task to develop the Christian community. A prominent evangelist during the early period of Christianity was the Apostle Paul. At first he was a persecutor of the Christians. However, his life changed radically after his encounter with the resurrected Jesus on the way to Damascus. This experience changed his life from a church persecutor to a militant evangelist. One of the missions described in the Acts of the Apostles was the missionary work in Ephesus (Acts 19:1-12). Ephesus was a city that became the center of commerce and rhetoric in Asia Minor. In that place, Paul preached the gospel and developed his congregation. In presenting this article, the author uses a descriptive or narrative method primarily to answer two basic questions: 1) What is the model and process of evangelization that the Apostle Paul carried out in his missionary in Ephesus, especially those narrated in Acts 19:1-12 ?; 2) What is the contribution of Paul's model of evangelization to modern evangelization? The author finds that the model and process of Paul's evangelization in Ephesus includes dialogue about the baptism of the Spirit, preaching in synagogues, teaching in